A Case of Montelukast-Induced Churg-Strauss Syndrome Associated with Liver Dysfunction. (9th July 2011) - Matsui, Keiji; Nishijima, Kosuke
Abstract : A 64-year-old woman was admitted to hospital due to protracted diarrhea and liver dysfunction. The patient was diagnosed as Churg-Strauss syndrome (CSS) due to asthma, paranasal sinusitis, hypereosinophilia, and polyneuropathy. There was a history of taking montelukast, a leukotriene receptor antagonist (LTRA), which is thought to have some relationship with CSS. The liver biopsy specimen showed eosinophilic infiltration and centrolobular fatty change. In this paper, we review the relationship between LTRA and CSS. Several lines of evidence suggest that leukotriene plays an important role in maintaining neural tissues. We also review the potential relationship between centrolobular fatty change and pivoxil-containing antibiotics, which was prescribed for sinusitis before admission. Carnitine deficiency induced by pivoxil-containing agents may cause impaired fatty acid oxidation in mitochondria.